Violence against indigenous children and adolescents in Venezuela - Roberto Briceño-León; Gloria Perdomo
Abstract: Research on violence in indigenous communities refers to traditional practices of competition for scarce goods and clashes with other populations over their territories. Violence against children is not described, and authors of some studies state a tradition of good treatment towards them. In our study we shows that the situation has changed and new forms of violence are affecting 725,000 inhabitants from 51 indigenous groups of Venezuela, especially those composed of children and adolescents. The method used was interviews with key informants and for secondary census, civil society data and journalists' reports. Results describe the existence of four types of violence: (a) structural violence, derived from the shortage of food and medicines that have caused deaths due to malnutrition and lack of medical attention, prostitution, girl trafficking and forced emigration; (b) violence of organized crime, which exercise control of illegal mining and affect the Yanomami and Pemón peoples, as workforce for the production of coca and drug trafficking with the Yupka people; and contraband of gasoline in the Wayúu people; (c) domestic violence due to cultural changes derived from new patterns of alcohol consumption or the use of physical punishment of children between Piaroa and Yekuana peoples; and (d) the illegal violence of the State for the imposition of mining with the Pemón people or the repression for the protests with the Warao and Inga peoples. In the article we show the great difference between the official discourse of protection of indigenous peoples and the realities of violence, criminal exploitation and violation of rights suffered by indigenous children and adolescents.